Laparoscopic Needle assisted Repair of Inguinal Hernia in Children in Manipal Teaching Hospital, Pokhara - Shrestha, Binod Bade; Shrestha, Sujan (Nepal Journal of Medical Sciences, 2019)
Introduction: There are numerous minimally invasive surgical techniques for repair of congenital inguinal hernia (CIH) in children. We present a unique needle-assisted laparoscopic inguinal hernia repair using 20-gauge intravenous cannula. This study aims to evaluate the safety and feasibility of this technique. Methods: This prospective descriptive study was conducted in 50 patients; aged 1-13 years; from February 2018 to May 2019; either admitted with the diagnosis of CIH or detected incidentally when operated for some other surgical conditions. CIH was repaired using single supraumbilical port and 2-0 prolene suture passed through 20-gauge intravenous cannula. Statistical analysis was done using SPSS 20. Results: A total of 56 hernias were repaired in 50 patients out of which five cases were detected incidentally on patients undergoing laparoscopic appendectomy. The bilateral CIH was present in six cases. The mean operative time was 18.20 ± 4.57 minutes; 17.36 ± 3.83 minutes for unilateral hernia and 24.33 ± 5.20 minutes for bilateral hernia. There was no difference in operative time when compared between gender (p=0.26). The complications were recurrence in 1(1.78%) case, hematoma around deep ring in 2 (3.57%) cases and puncture site bleeding in 2 (3.57%) cases. There were 35 (70%) male and 15 (30%) female. The contralateral occult hernias were noted in 5 (10%) cases. Conclusions: Single port laparoscopic repair of inguinal hernia using a 20-gauge intravenous cannula with non-absorbable suture is a safe, effective and feasible in resource poor settings. The postoperative complications are minimal which is similar to past studies.